Evidence for a Teratogenic Risk in the Offspring of Health Personnel Exposed to Ionizing Radiation?!. Issue 10 (October 2016) - Wiesel, Awi; Stolz, Gabriela; Queisser-Wahrendorf, Annette
Abstract : (Abstracted from Birth Defects Res A 2016;106:475–479) The adverse effects of ionizing radiation are known through studies on animal models, and further investigations are required to evaluate teratogenic effects and to develop effective protection measures. An exploratory finding from a study undertaken in 2011 revealed teratogenic effects on the infants of mothers working in the medical field, wearing a dosimeter, and potentially exposed to ionizing radiation.